2020
DOI: 10.1155/2020/9701860
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Temperature-Dependent Heat Source/Sink and Variable Species Diffusivity on Radiative Reiner–Philippoff Fluid

Abstract: The principle aim of the current communication is to scrutinize the impact of distinguished effects like variable thermal conductivity and variable molecular diffusivity on non-Newtonian Reiner–Philippoff fluid moving over a stretchable surface. The process of heat transfer is carried out in the presence of nonlinear thermal radiation, variable thermal conductivity, and heat generation/absorption. Furthermore, the study of mass transfer phenomena is carried out in the existence of variable molecular diffusivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
(65 reference statements)
4
16
0
Order By: Relevance
“…Saidulu et al [2] explored the coduct of MHD on radiative tangent hyperbolic nanofluid past an inclined stretchable surface and noticed that the velocity of the fluid diminishes owing to an increment in the magnetic number. Sajid et al [3] contemplated the impact of heat source/sink and species diffusivity on radiative Reiner-Philippoff fluid past a stretchable surface. Williamson fluid accompanied with MHD, heat source, and nonlinear thermal radiation was deliberated by Parmar [4] who concluded that temperature gradient augments on account of an enhancement in the thermal radiation effect.…”
Section: Introductionmentioning
confidence: 99%
“…Saidulu et al [2] explored the coduct of MHD on radiative tangent hyperbolic nanofluid past an inclined stretchable surface and noticed that the velocity of the fluid diminishes owing to an increment in the magnetic number. Sajid et al [3] contemplated the impact of heat source/sink and species diffusivity on radiative Reiner-Philippoff fluid past a stretchable surface. Williamson fluid accompanied with MHD, heat source, and nonlinear thermal radiation was deliberated by Parmar [4] who concluded that temperature gradient augments on account of an enhancement in the thermal radiation effect.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear thermal radiative heat flux in its full form is employed without the usual truncation of the higher‐order terms in the expansion. The flow equations regarding mass, momentum, energy, and concentration conservation are similar to those in Na, 8 Ahmed et al, 12 and Sajid et al 13 vy=ux, $\frac{\partial v}{\partial y}=-\frac{\partial u}{\partial x},$ uwduwdx+1ρτyσB2uρ+ga[α1(TT)+α2(TT)2]+ga[α3(CC)+α4(CC)2]=uux+vuy, ${u}_{{\rm{w}}}\frac{d{u}_{{\rm{w}}}}{dx}+\frac{1}{\rho }\frac{\partial \tau }{\partial y}-\frac{\sigma {B}^{2}u}{\rho }+{g}_{{\rm{a}}}[{\alpha }_{1}(T-{T}_{\infty })+{\alpha }_{2}{(T-{T}_{\infty })}^{2}]+{g}_{{\rm{a}}}[{\alpha }_{3}(C-{C}_{\infty })+{\alpha }_{4}{(C-{C}_{\infty })}^{2}]=u\frac{\partial u}{\partial x}+v\frac{\partial u}{\partial y},$ σB2u2ρcp+1ρcpyκ(T)Ty+1ρcpruwxv[B1eη(TwT)...…”
Section: Model Formulationmentioning
confidence: 73%
“…Nonlinear thermal radiative heat flux in its full form is employed without the usual truncation of the higher-order terms in the expansion. The flow equations regarding mass, momentum, energy, and concentration conservation are similar to those in Na, 8 Ahmed et al, 12 and Sajid et al 13 ∂ ∂…”
Section: Model Formulationmentioning
confidence: 77%
See 2 more Smart Citations